Bridging the quality gap in diagnosis and treatment of malaria. (22nd April 2020) - Ikeda, Daniel J; Gosling, Roly; Eliades, M James; Chung, Amanda; Murungu, Joseph; Agins, Bruce D
Abstract : Controlling and eliminating malaria will require intensified efforts to improve the quality of diagnosis and treatment argue Daniel Ikeda and colleagues